تاريخ الحركة النكارية – الحلقة الثانية - بن عميرة, محمد (مجلة التاريخ, 1986)
Keywords: Nukkarisme

Mise en scène des commerces maghrébins parisiens - Raulin, Anne (Terrain. Anthropologie & sciences humaines, 1986)
Dans le cadre d'une recherche menée sur les commerces dits ethniques dans le xiiie arrondissement à Paris — principalement asiatiques et maghrébins — une dimension tout à fait particulière de l'activité commerciale nous a paru intéressante à étudier : les signes de « présentation de soi » de l'établissement, sa mise en scène propre. Il convient dans un premier temps de préciser les caractéristiques du cadre dans lequel s'effectue l'analyse. Le commerce dit ethnique — dont la définition même p...
Keywords: Commerce -- Djerba

The Zanzibar Archives Project - Thurston, Anne (Information Development, 1986)
While the importance of archives administration and records management is beginning to be realized in the developing world, few governments have recognized the contribution well-kept records could make to development and efficient public administration. Two workshops, attended by members of the staff of seven National Archives in East and Central Africa, were held in Zanzibar in 1984 and 1985. Initially inspired by the Royal Geographical Society's concern for the condition of correspondence from and about explorers, the workshops examined the problems on the ground of preserving and making records accessible. Work on the Ministry of Agriculture's records demonstrated their development value and the need for a concerted training programme within the region.
Keywords: Archives -- Zanzibar

L. Valensi et A. L. Udovitch, Juifs en terre d'Islam, les communautes de Djerba. Paris-Montreux, Editions des Archives contemporaines, 1984. 182 p. - Bolens, Lucie (Revue suisse d'histoire, 1986)
Keywords: Recension

Review of Women and Community in Oman; Contemporary Yemen: Political and Historical Background - Spencer, William (The Annals of the American Academy of Political and Social Science, 1986)
Keywords: Recension

Werner Schwartz, Die Anfänge der Ibaditen in Nordafrika. Der Beitrag einer islamischen Minderheit zur Ausbreitung des Islams, Studien zum Minderheitenproblem im Islam, Bd. 8, Wiesbaden, in Kommission bei Verlag O. Harrassowitz (Coll. «Bonner Orientalistische Studien», NS, Bd. 27/8), 1983; 15 x 21, 352 p., avec biblio., index et deux cartes - Gilliot, Claude (Arabica, 1986)
Keywords: Recension

Thomas Bierschenk: Weltmarkt, Stammesgesellschaft und Staatsformation in Südostarabien (Sultanat Oman), (Bielefelder Studien zur Entwicklungssoziologie/Bielefeld Studies on the Sociology of Development.23.). Saarbrücken u.a. : Breitenbach 1984. xv, 400 S. 8°. ISBN 3-88156-260-5. DM 40,-. - Schwartz, Werner (Die Welt des Islams, 1986)
Keywords: Recension

Review of Women and Community in Oman - Joseph, Suad (American Ethnologist, 1986)
Keywords: Recension

Review of Sohar: Culture and Society in an Omani Town.; Behind the Veil in Arabia: Women in Oman. - Kielstra, Nico (Middle East Report, 1986)
Keywords: Recension

Review of This Is Oman 1985 - McBeath, Neil (Bulletin (British Society for Middle Eastern Studies), 1986)
Keywords: Recension

Lethielleux (Jean) : Ouargla, cité saharienne. Des origines au début du XXe siècle - Frémeaux, Jacques (Outre-Mers. Revue d'histoire, 1986)
Keywords: Recension

Abu Zakariya' Yahyâ b. Abi Bakr : Kitâb al-Sîra wa-ahbâr al-a'imma, éd. critique 'Abd Ayyüb, Tunis. MTE. 1985, 443 p. - (Revue de l'Institut des Belles Lettres Arabes, 1986)
On attendait depuis longtemps l'édition de cet ouvrage qui représente le plus ancien récit ibâdite sur l'histoire de ce mouvement au Maghreb. Originaire de Wargilân (Ouargla}. l'auteur écrivit sa chronique probablement vers la fin du 5ème/11ème siècle. On ne disposait jusqu'à présent que de traductions françaises partielles : l'une faite sur des manuscrits défectueux par E. Masqueray en 1878 : l'autre due à R. Le Tourneau et R. Idris, sur un texte établi par Ch. Dalet (Revue Africaine 1960, 99-176. 322·390; 1961, 117-176, 323-374). La présente édition repose sur deux manuscrits fort récents (celui du Caire date de la fin du 19ème siècle, celui de Tunis de 1927) ; l'éditeur a confronté les deux textes à la traduction parue dans la Revue Africaine dont la publication fut d'ailleurs interrompue par suite de la disparition de la revue en 1961. Il est dommage que l'éditeur ne dise rien des autres copies qui, malgré leurs défauts, ne doivent pas manquer d'intérêt. Son travail n'est cependant pas à sous-estimer, car il nous donne accès à une oeuvre essentielle pour la connaissance de l'ibadisme maghrébin.
Keywords: Recension

Tabias et jessour du Sud tunisien : Agriculture dans les zones marginales et parade à l'érosion - Bonvallot, Jacques (Cahiers de l'Orstom, 1986)
Keywords: Agriculture -- Djerba

Udovitch and Valensi: The Last Arab Jews: The Communities of Jerba, Tunisia - Stillman, Norman A. (Middle East Journal, 1986)
Keywords: Recension

The Dutch on the Swahili Coast, 1776-1778: Two Slaving Journals, Part I - Ross, Robert; Holtzappel, Fk. G. (The International Journal of African Historical Studies, 1986)
Keywords: Esclavage -- Zanzibar

Judisches Erbe arabischer Lander - Freund, Wolfgang Slim (Orient : Zeitschrift fur Politik und Wirtschaft des Orients‎‎, 1986)
Keywords: Judaïsme -- Djerba

Review: Kitāb Ibn Sallām: eine Ibaditisch-Magribinische Geschichte des Islams aus dem 3./9. Jahrhundert by Werner Schwartz; Šaih̬ Sālim ibn Ya'qūb - Francesca, Ersilia (Annali dell'Istituto Universitario Orientale di Napoli, 1986)
Keywords: Recension

Interior Oman - Melamid, Alexander (Geographical Review, 1986)

Tanfust n sen Aytma : l'apologue des deux frères - Aït Akakus (Awal. Cahiers d'études berbères, 1986)
Keywords: Littérature -- Mzab

Les poèmes nautiques d'Ahmad ibn Māǧid 2eme partie les poèmes àrime unique: al-qaṣā'id texte arabe établi avec introduction et analyse en français - Khoury, Ibrahim (Bulletin d'Études Orientales, 1986)
Keywords: Navigation -- Oman

Some Remarks about Sectarian Movements in al-Andalus - Aguade, Jorge (Studia Islamica, 1986)
Keywords: Nukkarisme -- Andalousie

From sacred history to historical memory and back: The Jewish past - Valensi, Lucette (History and Anthropology, 1986)
Keywords: Judaïsme -- Djerba

On the Quietist and Activist Traditions in Islamic Political Writing - Lewis, Bernard (Bulletin of the School of Oriental and African Studies, 1986)

The Zanzibar Archives project and its implications for the preservation of records in East and Central Africa - Thurston, Anne (African Research and Documentation, 1986)
Keywords: Zanzibar

Les communautés ibāḍites au Maghreb: réflexions sur leur rapport au pouvoir, à la sexualité et à la mort - Gouja, Moncef (Peuples Méditerranéens, 1986)
Keywords: Moeurs et coutumes -- Ibadisme

Muslim Responses to French Imperialism: An Algerian Saharan Case Study - Holsinger, Donald C. (The International Journal of African Historical Studies, 1986)
The political events that preceded French occupation of Mīzāb, based mainly on French archivial materials. The awkward position of the Mīzābīs between French superior military power, which could easily destroy their trading activities in the North if they would not submit to French demands, and the threat of attaques on them by rebels in the South and their nomadic supporters if they would openly submit to the French and support them. This dilemma led to fierce internal strife in Mīzāb.
Keywords: Emigration -- Mzab -- Algérie

The Arabs in Zanzibar: from Sultanate to People’s Republic - Lodhi, Abdulaziz Y. (Journal of the Institute of Muslim Minority Affairs, 1986)
Keywords: Zanzibar

Ibāḍī political and administrative organisations in the stage of secrecy with special reference to North Africa - Khulayfāt, ʿAwaḍ Muḥammad (The Maghreb Review, 1986)

Professions de foi ibadites: Contribution à l'étude de l'ibadisme et de sa théologie - Jaabiri, Farhat (Revue de l'Institut des Belles Lettres Arabes, 1986)
Keywords: Recension

Les Jerbiens en Tunisie. Réminiscences d’un sociologue allemand devant une recherche inachevée - Freund, Wolfgang Slim (Revue de l'Institut des Belles Lettres Arabes, 1986)
Abstract (p. 57): departing from his book of 1970, the author explains the reasons that made him doubt the validity of Weber’s sociological models and categories for understanding the economic success of Jerban (and Mīzābī) merchants. In a second part of his article the author indicates guidelines for a more objective sociological understanding of the Jerban phenomenon.
Keywords: Commerce -- Djerba

Ṣināʿa al-maḥāllī wa’l-nasīj fī Jarba (Les Cahiers de l'animation, 1986)
Keywords: Artisanat -- Djerba

al-māʾatim bi-Ṣidghiyān (Les Cahiers de l'animation, 1986)
Keywords: Moeurs et coutumes -- Djerba

Jarba, al-aghniyya al-shaʿbiyya bi-Mīdūn (Les Cahiers de l'animation, 1986)
Keywords: Musique -- Djerba

Iḥtifālāt al-zawāj bi-Ṣadġiyān, Jarba - Bashīnī, Kamāl al-; Ibn Ḥalīma, Munīra (Les Cahiers de l'animation, 1986)
Keywords: Moeurs et coutumes -- Djerba

The Sultanate of Oman: International Symposium on the Traditional Music of Oman - Scarce, Jennifer M. (Bulletin (British Society for Middle Eastern Studies), 1986)
Keywords: Musique -- Oman

Sakrale und profane Ambivalenzen: zum Problem der politischen Legitimation im modern Oman - Rothholz, Walter (Orient, 1986)

The early Islamic movement of the Kharidjites and modern Moslem extremism: similarities and differences - Jansen, Johannes J.G. (Orient, 1986)
Keywords: Kharijisme

Banū Mukram in Oman - Ezzah, Abdullah M. Abu (Proceedings of the Seminar for Arabian Studies, 1986)

Cultural ecological theory and the formation of the Ibadite desert confederacy - Bennoune, Mahfoud (Dialectical Anthropology, 1986)
Keywords: Urbanisme -- Mzab

Ulrich Rebstock: Die Ibāditen im Magrib (2./8.–4/10.Jh.): die Geschichte einer Berberbewegung in Gewand des Islam. (Islamkundliche Untersuchungen, Bd. 84.) xxviii, 366 pp. Berlin: Klaus Schwarz Verlag, 1983. - Werner Schwartz: Die Anfänge der Ibaditen in Nordafrika: der Beitrag einer islamischen Minderheit zur Ausbreitung des Islams. (Bonner Orientalistische Studien. N. S. Bd. 27. Studien zum Minderheitenproblem im Islam, 8.) 349 pp., 2 maps. Wiesbaden: Otto Harrassowitz, 1983. - Brett, Michael (Bulletin of the School of Oriental and African Studies, 1986)
Keywords: Recension

يزيد بن المهلب بن أبي صفرة الأزدي فاتح شطر ما وراء النهر وشطر خرسان وشطر طبرستان - خطاب, محمود شيت (مجلة المجمع العلمى, 1986)

حكم يزيد بن عبدالملك 101 - 105هـ / 720 - 724م : وجهة نظر تحليلية - حسين, خليل شاكر (آداب الرافدين, 1986)

الاجتهاد في المذهب الإباضي - بالحاج, محمد الشيخ (الدراسات الإسلامية, 1986)
Keywords: Ijtihad

Introduction à l’étude de l’ibāḍisme et de sa théologie, written by Pierre Cuperly - Déjeux, Jean (Maghreb-Machrek, 1986)
Keywords: Recension

Jean Lethielleux, Ouargla, cité saharienne: des origines au début du xx e siécle. (Documents d' Histoire Maghrebienne, Tom. iv.) x, 298 pp. map, 16 Plates. Paris: Librairie Orientaliste Paul Geuthner, 1983. Fr. 150. - Norris, Harry Thirlwall (Bulletin of the School of Oriental and African Studies, 1986)
Keywords: Recension

Lithic Raw Materials of the Late Palaeolithic/Neolithic Industries in Jabal Nefusa, Tripolitania - Mrazek, Ivan; Svoboda, JIŘÍ (Anthropologie, 1986)
The mineralogic-petrographical character of the raw materials of the Late Palaeolithic/Neolithic stone industries, collected at several open air-sites in the area of Jabal Nefusa, have been studied and the origin of the raw materials have been recognized. Two types of Upper Cretaceous (Nalut Formation) cherts (the coloured and the striped ones), used for the manufacture of implements, have been distinguished. They may be considered either local or short-distance imported raw materials.
Keywords: Géologie -- Djebel Nefousa

Struggle between the Portuguese and the Arabs of Oman for supremacy in the Persian Gulf and the Indian Ocean - Ali, Abdul (Hamdard Islamicus, 1986)
Keywords: Relations -- Oman -- Portugal

L'habitat mozabite au M'zab - Bousquet, Christian (Annuaire de l'Afrique du Nord, 1986)
Keywords: Urbanisme -- Mzab

Le M'Zab - Lumières du Mzab - Moriaz, Jean (Le Saharien, 1986)
Keywords: Moeurs et coutumes -- Mzab

Deux textes de l'Oued Mzab - Ighoulad, Brahim (Études et Documents Berbères, 1986)
Keywords: Littérature -- Mzab

Opération "retrouvailles" ou "30 ans après... du Fezzan à Ghardaïa, à Trelex en Suisse - Godard, Jean (Le Saharien, 1986)

Les nouveaux citadins de Beni Isguen au M'zab (Sahara algérien) - Bousquet, Christian (Urbama, 1986)
Keywords: Urbanisme -- Mzab

Alternanze accentuali e morpho-sintassi nominale nel berbero orientale, Contributi di orientalistica, glottologia e dialettologia - Brugnatelli, Vermondo (Quaderni di Acme, 1986)
Keywords: Linguistique

Some Relations between three Piyutim from Djerba and three Arab Songs - Davis, Ruth Frances (The Maghreb Review, 1986)
Keywords: Judaïsme -- Djerba

Late Quaternary deformed shorelines in Tunesia - Richards, G. W. (Zeitschrift für Geomorphologie. Supplementband, 1986)
Keywords: Géologie -- Djerba

Les commerçants étrangers dans l'agglomération parisienne - Ma Mung, Emmanuel; Guillon, Michelle (Revue européenne des migrations internationales, 1986)
Keywords: Emigration -- Djerba -- France

Etude des fréquences alléliques des systèmes ABO, Rhésus, C3 et BF chez les Juifs et les Noirs de l’île de Djerba (Tunisie) - Helal, Ahmed Noureddine; Toumi, Nh.; Boukef, M. K.; El Gaied, A. (Le pharmacien du Maghreb, 1986)
Keywords: Biologie -- Djerba

L'homme méditerranéen et la mer. Actes du Troisième congrès international d'études des cultures de la Méditerranée occidentale (Jerba, avril 1981), Micheline Galley et Leïla Ladjimi sebai éds, Tunis, Les Éditions Salammbô ; Paris, diffusion De Boccard, 1985. - Fontenay, Michel (Annales. Histoire, Sciences Sociales, 1986)
Keywords: Recension

De l'Africa latino-chrétienne à l'Ifriqiya arabo-musulmane : questions de toponymie - Beschaouch, Azedine (Comptes-rendus des séances de l'année, 1986)
Keywords: Antiquité; Archéologie -- Djerba